Peningkatan Literasi dan Numerasi Siswa Sekolah Dasar melalui Pendekatan Berbasis Proyek di SD IT Hidayatullah - Eka Ima Mirawati; Akbar Al Masjid; Pardimin Pardimin (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
By using a project-based method, this classroom action research seeks to ascertain if sixth-grade students at SD IT Hidayatullah have improved their literacy and numeracy abilities. Three cycles of preparation, action execution, observation, and reflection encompass the research. 28 sixth graders in the even semester of the 2024–2025 school year served as the research subjects. Teacher interviews, project performance evaluations, and observations were used to gather data. The findings demonstrate how project-based learning can improve students' active participation, comprehension of texts, and practical application of numeracy principles. The average literacy and numeracy scores in the first cycle were 72.8 and 70.4, respectively; in the second cycle, they increased to 86.2 and 83.7. In cycle III there was a significant increase in literacy, increasing to 100 and numeracy 98.8. This increase demonstrates the effectiveness of the project approach as a contextual and meaningful learning strategy